Pengaruh Brand Image Terhadap Minat Beli Produk Kaos Brand Adlv Melalui Brand Trust Pada Konsumen di Kabupaten Sidoarjo - Deva Arya Wiguna; Afifatus Sholikhah (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. This study aims to analyze the influence of Brand Image on Purchase Intention of ADLV brand t-shirt products through Brand Trust as a mediating variable among consumers in Sidoarjo Regency. The widespread circulation of counterfeit (KW) ADLV products in the market has created a gap between consumers' visual appeal toward brand image and actual purchasing decisions, making brand trust a crucial factor that needs to be examined. This research employs a quantitative approach using a survey method through questionnaire distribution to 120 People its selected using incidental sampling technique. Respondent criteria included residing in Sidoarjo Regency, knowing or having seen ADLV brand t-shirt products, and being at least 17 years old. The data were analyzed using the Partial Least Squares (PLS) approach with SmartPLS 4.0 software. These findings indicate that Brand Trust has a more dominant role compared to Brand Image in driving consumer purchase intention. Therefore, ADLV's marketing strategy in Sidoarjo Regency needs not only to maintain a strong brand image but also to actively build consumer trust through product information transparency, authenticity guarantees, and quality consistency to overcome the challenge of counterfeit products in the market.